Causes of anemia in patients with gastric cancer during the perioperative period - M. A. Giparovich; M. D. Khanevich; E. Yu. Yuryev; A. E. Alborov; E. R. Shilova (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE of the study was to reveal the causes of anemia in patients with gastric cancer in the perioperative period.METHODS AND MATERIALS. The object of the study were 700 patients with gastric cancer who underwent surgical treatment. All patients underwent clinical and biochemical blood test, indicators characterizing iron metabolism in the body (serum iron, ferritin, transferrin), and the level of endogenous erythropoietin during the perioperative period. The comparison group included 20 patients with gastric bleeding of non-neoplastic etiology. Both groups were comparable in age (median was 60 and 62 years old) and hemoglobin level (median Hb 95.3 g/l and 94.5 g/l).RESULTS. Anemia was diagnosed in 15 % of patients (n=105) in the perioperative period. Mild anemia was more often detected (hemoglobin level 95–110 g/l) – in 47.6 % of patients. Moderate anemia (80–94 g/l) was observed in 24.0 % of patients, severe anemia (65–79 g/l) – in 18.1 % of patients, severe (hemoglobin level below 65 g/l) – in 10.3 % of patients. A strong correlation (r=0.89; P<0.05) was observed between the stage at the tumor process and the severity of anemia. At the same time, no connection was found between the macroscopic form of a stomach tumor and the severity of anemia. The analysis of the indicators of iron metabolism allowed to confirm the true iron deficiency in this category of patients, which was characterized by a decrease in the level of serum iron in patients with gastric cancer to (7.8±1.6) μmol/L (from 4.7 to 8.2 μmol/L). Comparative analysis of the level of endogenous erythropoietin in the group of patients with gastric cancer (n=20) and patients with gastrointestinal bleedings of non-neoplastic etiology (n=20) showed significantly lower values   with a difference of 27.7 % in the first group of patients ((66.9±28.2) mIU/ml versus (95.6±36.7) mIU/ml; P<0.05), which indicated inadequate production of erythropoietin in patients with gastric cancer.CONCLUSION. The main causes of anemia in patients with gastric cancer in the perioperative period should be considered a true iron deficiency, as well as inadequate production of endogenous erythropoietin.